Phylogeny and Characteristics of Yersinia pseudotuberculosis strains from the Aksai High-Mountain and Balkhash Desert Foci of Plague - G. A. Eroshenko; A. K. Dzhaparova; K. A. Nikiforov; A. S. Sidorin; L. M. Kukleva; N. S. Chervyakova; Ya. M. Krasnov (Проблемы особо опасных инфекций, 2024)
The aim of the study is to obtain a comprehensive characterization of Yersinia pseudotuberculosis strains from the Aksai high-mountain and Balkhash desert foci of plague in Central Asia. Materials and methods. Investigation of the cultural, morphological and biochemical properties of the examined strains was carried out using conventional methods of laboratory diagnostics. Ion S5 XL System (Thermo Fischer Scientific) was used for whole-genome sequencing. Data processing and sequence assembly of raw reads de novo were performed using Ion Torrent Suite software package 5.12 and Newbler gsAssembler 2.6 (454 Life Sciences). To search for marker SNPs, the Wombac 2.0 program based on the BioLinux 8.0 operating system was applied. When constructing the dendrogram, the Maximum Likelihood method, the PhyML 3.1 program and the HKY85 model were used. Results and discussion. The studied strains from the Aksai high-mountain and Balkhash desert foci have properties characteristic of the Y. pseudotuberculosis species, are prototrophs and do not contain the pYV plasmid. According to phylogenetic analysis based on identified 109,641 core SNPs, they are closely related to strains of the pseudotuberculosis microbe from the Sarydzhaz high-mountain focus in the Kyrgyz Republic and the Republic of Kazakhstan, as well as to the O:3 serovar strain from Turkmenistan. The cluster of these Central Asian strains on the phylogenetic tree of Y. pseudotuberculosis is localized next to strains of the pseudotuberculosis microbe of O:3 serovar from various regions of the world. The results obtained testify to the circulation of a separate phylogeographic population of Y. pseudotuberculosis in the territory of natural plague foci in Central Asia. The characterized Y. pseudotuberculosis strains and their whole genome sequences can be used as reference ones for the Aksai and Balkhash natural plague foci of Central Asia.